2021
DOI: 10.3390/biomedicines9070818
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Obesity on Lymphatic Pain and Swelling in Breast Cancer Patients

Abstract: Lymphatic pain and swelling due to lymph fluid accumulation are the most common and debilitating long-term adverse effects of cancer treatment. This study aimed to quantify the effects of obesity on lymphatic pain, arm, and truncal swelling. Methods: A sample of 554 breast cancer patients were enrolled in the study. Body mass index (BMI), body fat percentage, and body fat mass were measured using a bioimpedance device. Obesity was defined as a BMI ≥ 30 kg/m2. The Breast Cancer and Lymphedema Symptom Experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 26 publications
0
5
0
1
Order By: Relevance
“…Se sabe que el estrés psicosocial es un factor predisponente y de riesgo potencial para presentar y exacerbar los síntomas de la DP por somatización del evento desencadenante (1,40,52,53), por lo que no es una coincidencia que la mayor parte de las estudiantes en este estudio pertenezca a la facultad de medicina, cuyo estilo de vida es particularmente estresante, más que otras carreras, como ha sido reportado por varios autores (47,54). Esto se ha visto reforzado sobre todo en estos últimos años, considerando las grandes demandas académicas que atraviesan en su día a día, laborales y emocionales durante las pasantías, la paralización frecuente de las clases presenciales, las tomas de decisiones constantes frente al sufrimiento de los pacientes asignados, insatisfacción con la elección universitaria y profesional, así como las condiciones de los puestos de trabajo a nivel hospitalario y en las aulas de clases, carentes de recursos básicos, en su gran mayoría, y ahora agregándose la pandemia por la COVID-19, lo que hace que la población de los profesionales de la salud, incluyendo a los estudiantes, sea caracterizada como vulnerable al momento de somatizar y exacerbar signos y síntomas presentes (54)(55)(56)(57)(58)(59).…”
Section: Resultsunclassified
“…Se sabe que el estrés psicosocial es un factor predisponente y de riesgo potencial para presentar y exacerbar los síntomas de la DP por somatización del evento desencadenante (1,40,52,53), por lo que no es una coincidencia que la mayor parte de las estudiantes en este estudio pertenezca a la facultad de medicina, cuyo estilo de vida es particularmente estresante, más que otras carreras, como ha sido reportado por varios autores (47,54). Esto se ha visto reforzado sobre todo en estos últimos años, considerando las grandes demandas académicas que atraviesan en su día a día, laborales y emocionales durante las pasantías, la paralización frecuente de las clases presenciales, las tomas de decisiones constantes frente al sufrimiento de los pacientes asignados, insatisfacción con la elección universitaria y profesional, así como las condiciones de los puestos de trabajo a nivel hospitalario y en las aulas de clases, carentes de recursos básicos, en su gran mayoría, y ahora agregándose la pandemia por la COVID-19, lo que hace que la población de los profesionales de la salud, incluyendo a los estudiantes, sea caracterizada como vulnerable al momento de somatizar y exacerbar signos y síntomas presentes (54)(55)(56)(57)(58)(59).…”
Section: Resultsunclassified
“…4 Lymphedema is a chronic, progressive, and debilitating complication and one of the most common side effects of breast cancer treatment, which results from the fluid accumulation in the interstitial tissue due to damage to the lymphatic system following surgery, radiography, or tumor. [12][13][14][15] Breast cancer-related lymphedema (BCRL) symptoms impose high costs on patients and increase their distress, reduce the quality of life (QOL), and lead to disability. 16 More than one-fifth of women who survive breast cancer develop lymphedema after breast cancer treatment, affecting more than 40% of the three million breast cancer survivors in the United States.…”
Section: Background and Significancementioning
confidence: 99%
“…Abbreviation: SD, standard deviation. Note: All questions were scored in a range of 0 to 9.Applied Clinical Informatics Vol 13. No.…”
mentioning
confidence: 99%
“…Some studies found a positive correlation between BMI and PMPs [79], but at the same time, some studies showed no correlation between them [17,46]. In patients with high BMI, axillary clearance is more challenging due to more adipose tissue, which may affect the treatment of intercostal brachial nerve, so the patients may face a higher risk of pain and sensory impairment.…”
Section: Obesitymentioning
confidence: 99%